1999
DOI: 10.1046/j.1365-2168.1999.00977.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathology and outcome of surgical treatment for lithium-associated hyperparathyroidism

Abstract: Hyperparathyroidism associated with lithium may be due to either parathyroid hyperplasia or adenoma. Observations in the present study supported a true cause and effect relationship. Routine bilateral neck exploration should be performed because of a relatively high frequency of multigland involvement. However, parathyroid resection should be limited to evident disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
2
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 12 publications
1
40
2
2
Order By: Relevance
“…Of these, 71 patients had surgically verified hyperparathyroidism of whom 42 patients were found to have adenomas (Garfinkel et al, 1973;Christensson, 1976;MacGregor, 1977;Toffaletti et al, 1979;Graze, 1981;Ananth and Dubin, 1983;McHenry et al, 1990;Nordenstrom et al, 1992;Abdullah et al, 1999;Awad et al, 2003;Dalan et al, 2007;Rizwan and Perrier, 2009;Szalat et al, 2009). In addition, 29 patients were found to have diffuse parathyroid hyperplasia (Cairns et al, 1985;Krivitzky et al, 1986;McHenry et al, 1990;Feldman and Pachman, 1990;Tissel et al, 1991;Nordenstrom et al, 1992;Abdullah et al, 1999;Awad et al, 2003;Hundley et al, 2005;Rizwan and Perrier, 2009;Szalat et al, 2009). In the remaining case reports, hyperparathyroid states were not surgically verified (Cervi-Skinner, 1977;Toffaletti et al, 1979;Herman, 1981;Davis et al, 1981;Rothman, 1982;Shen and Sherrard, 1982;Ananth and Dubin, 1983;Prasad, 1984;Mallette and Eichhorn, 1986;Rifai et al, 2001;Bilanakis and Gibiriti, 2004;Sloand and Shelly, 2006).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Of these, 71 patients had surgically verified hyperparathyroidism of whom 42 patients were found to have adenomas (Garfinkel et al, 1973;Christensson, 1976;MacGregor, 1977;Toffaletti et al, 1979;Graze, 1981;Ananth and Dubin, 1983;McHenry et al, 1990;Nordenstrom et al, 1992;Abdullah et al, 1999;Awad et al, 2003;Dalan et al, 2007;Rizwan and Perrier, 2009;Szalat et al, 2009). In addition, 29 patients were found to have diffuse parathyroid hyperplasia (Cairns et al, 1985;Krivitzky et al, 1986;McHenry et al, 1990;Feldman and Pachman, 1990;Tissel et al, 1991;Nordenstrom et al, 1992;Abdullah et al, 1999;Awad et al, 2003;Hundley et al, 2005;Rizwan and Perrier, 2009;Szalat et al, 2009). In the remaining case reports, hyperparathyroid states were not surgically verified (Cervi-Skinner, 1977;Toffaletti et al, 1979;Herman, 1981;Davis et al, 1981;Rothman, 1982;Shen and Sherrard, 1982;Ananth and Dubin, 1983;Prasad, 1984;Mallette and Eichhorn, 1986;Rifai et al, 2001;Bilanakis and Gibiriti, 2004;Sloand and Shelly, 2006).…”
Section: Resultsmentioning
confidence: 96%
“…Among cross-sectional studies of hypercalcemia and hyperparathyroidism in lithium-treated patients, duration of lithium therapy has ranged from 1 month to 30 years (Table 1). Lithium-associated hyperparathyroidism also does not appear to be related to lithium dosing and is not a result of lithium toxicity (Abdullah et al, 1999;El Khoury et al, 2002).…”
Section: Epidemiology Of Lithium-associated Hyperparathyroidismmentioning
confidence: 97%
“…Four of the included studies recommended MIP [5,7,9,10], and 5 recommended bilateral exploration [11,12,27,28,29] (table 7). …”
Section: Discussionmentioning
confidence: 99%
“…McHenry et al (33) also report three cases of associated thyroid carcinoma among a series of eight patients undergoing parathyroidectomy for LAH and Abdullah et al also describe one case of occult PTC among 11 patients with LAH (20). An increased prevalence of up to 2% associated occult thyroid malignancy and PTA in patients undergoing neck surgery for parathyroidectomy (34), and it was suggested that thyroid evaluation before such a surgical procedure is mandatory and simultaneous thyroidectomy should be considered.…”
Section: The Association Of Lah and Thyroid Carcinomamentioning
confidence: 99%